Use of Lung Ultrasound and Thoracic Fluid Content for Prediction of non-Invasive Ventilation Failure in Neonates - Elgendy, Essam Mahmoud; Elmahdy, Heba Saied; Elatif Nassar, Mohamed Abd; Eltomey, Mohamed Adel; Elsharkawy, Hamed Mohamed (Journal of Neonatal Surgery, 2025)
Purpose: Non-invasive ventilation (NIV) is commonly employed as the primary respiratory support modality in neonates with respiratory distress due to its lower risk of complications compared to invasive mechanical ventilation. This research aimed to compared between lung ultrasound and thoracic fluid content (TFC) as early predictive tools for identifying NIV failure in premature neonates. Methods: This prospective cohort observational research involved 60 preterm neonates aged from 28 to 35 weeks old, both sexes, suffered from respiratory distress syndrome which were candidate to NIV. Patients were categorized into two equal groups: Group I: Nasal CPAP (continuous positive airway pressure) and gestational age (GA) 28-35 W and group II: nasal intermittent mandatory ventilation and GA 28-35 W. Results: Lung ultrasound score (LUS) strongly associated with TFC in the case of NIV failure. The LUS score demonstrated a marked increase in the group that experienced failure opposed to the group that succeeded. Additionally, TFC measured via EC in NIPPV was significantly elevated in the failure group opposed to the success group. Conclusions: LUS score correlates well with TFC, in the case of NIV failure and it may serve as a valuable tool for tracking changes in lung aeration during the early application of NIV in premature infants.